Locating Consolidation Centres For Aggregation of Subsistence Agricultural Products From The Southwestern Region of Nigeria - Sulaimon Adebiyi; Jonathan Ekpudu; Olamide Awe (Journal of Transportation and Logistics)
The purpose of this study is to improve agriculture product supply capacity in a way that is beneficial for subsistence farmers and consolidators in the southwestern region of Nigeria. Data gathered includes the distance travelled between various locations, units demanded, and fixed and variable costs. The data were presented on Google maps and evaluated using Weber, Centre of Gravity (CoG), and Mixed Integer Linear Program (MILP) methods. Software deployed for analysis were Microsoft 2013-Excel Solver, and Statistical Analysis System (SAS). The Weber and CoG methods yielded similar results that the consolidation centre should be located at the Oshodi area of Lagos State to minimise distance travelled. However, the MILP model suggested that opening consolidation centres at the Mushin area of the Southwest region generated the optimal outcome in terms of cost and distance travelled to market and customers. The novelty of the developed model is that it provides alternative location candidates that can be critically explored in practical location decisions. Hence, the model is a support tool applicable by managers of agricultural businesses in their decision to establish consolidation centres in such a manner that minimises cost and distance travelled to meet customer and market demand.